2021
DOI: 10.3390/ph15010053
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a Therapeutic Target of Natural Products Enhancing Embryo Implantation

Abstract: Infertility is an emerging health issue worldwide, and female infertility is intimately associated with embryo implantation failure. Embryo implantation is an essential process during the initiation of prenatal development. Recent studies have strongly suggested that autophagy in the endometrium is the most important factor for successful embryo implantation. In addition, several studies have reported the effects of various natural products on infertility improvement via the regulation of embryo implantation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 251 publications
0
4
0
Order By: Relevance
“…IL1B is shown to participate in implantation by indirectly increasing concentration of intracellular cAMP by upregulating PTGS2 and PGE2, thus reorganizing the actin cytoskeleton [ 33 ]. It is demonstrated that in the mid-to-late-secretory phase endometrium, where implantation occurs, and the concentrations of ovarian steroid hormones are highest, high expression levels of cytokines such as LIF and IL6 are detected [ 38 ]. Immune cells, such as dNK, play a role in pathological pregnancy and are related to preeclampsia, recurrent pregnancy loss, endometriosis, and recurrent implantation failure (RIF).…”
Section: Discussionmentioning
confidence: 99%
“…IL1B is shown to participate in implantation by indirectly increasing concentration of intracellular cAMP by upregulating PTGS2 and PGE2, thus reorganizing the actin cytoskeleton [ 33 ]. It is demonstrated that in the mid-to-late-secretory phase endometrium, where implantation occurs, and the concentrations of ovarian steroid hormones are highest, high expression levels of cytokines such as LIF and IL6 are detected [ 38 ]. Immune cells, such as dNK, play a role in pathological pregnancy and are related to preeclampsia, recurrent pregnancy loss, endometriosis, and recurrent implantation failure (RIF).…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocytes that have become overly active may injure normal tissues that display the target antigen, putting healthy cells at risk in addition to targeting viral antigens. Regular cells produce neoantigens, cancer antigens, and auto-antigens in reaction to cell disruption caused by cytotoxic T lymphocytes, worsening the injury by 'targeting' body cells [80]. Furthermore, activation of Th1 and Th17 T cells after CAR-T cell therapy increases serum cytokine output, like IFN-, IL-17, and IL-6, which typically leads to cytokine release syndrome (CRS).…”
Section: Mechanisms Underlying Iraes (Immune Related Adverse Events)mentioning
confidence: 99%
“…Hence, natural product as autophagy modulator has been proposed, owing to their safe profiles whilst showing high effectiveness to diminish tumor cells ( Zhang Q. Y. et al, 2018 ; Rahman et al, 2020 ; Al-Bari et al, 2021 ). Natural product to regulate autophagy is also a novel therapeutic approach in improving fertility ( Zhu et al, 2019 ; Park et al, 2021 ). In addition, natural products can be used to target multiple pathways, thus providing greater flexibility and potential for a variety of cancer types and stages.…”
Section: The Role Of Autophagy In Reproductive Cancermentioning
confidence: 99%